1997
DOI: 10.1042/bj3220145
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leptin and β3-adrenergic receptors in rat adipose tissue in altered thyroid states

Abstract: The level of leptin [the obese (ob) gene product] mRNA is markedly elevated in hypothyroid male rats. The administration of tri-iodothyronine (T3) to hypothyroid rats resulted in a 40% decrease in leptin mRNA at 8 h. This decrease in leptin mRNA was associated with a parallel decline in circulating leptin levels of about 50% at 24 h. Conversely, beta 3-adrenergic receptor mRNA levels were markedly decreased in epididymal adipose tissue from hypothyroid rats. T3 administration resulted in a 147% increase at 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 53 publications
11
42
0
3
Order By: Relevance
“…In light of these results, alterations in thyroid status might lead to compensatory changes in circulating leptin. Thus, our findings are in agreement with some studies and support an inverse relationship between thyroid activity and leptin production within the adipose tissue [18,20,21].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In light of these results, alterations in thyroid status might lead to compensatory changes in circulating leptin. Thus, our findings are in agreement with some studies and support an inverse relationship between thyroid activity and leptin production within the adipose tissue [18,20,21].…”
Section: Discussionsupporting
confidence: 82%
“…Fain et al observed increased mRNA expression of leptin in adipocytes of hypothyroid rats, and a reduction in expression in response to T3 treatment [20]. A recent study showed that TSH releases leptin by a direct action at the adipocytes in human adipose tissue via the presence of TSH receptors in adipose tissue [21].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, one would expect an inhibitory effect of thyroid hormones on leptin secretion, since thyroid hormones have a permissive role on the effects of catecholamines on betaadrenergic receptors, and since stimulation of these receptors suppresses leptin expression (231). This seems consistent with the inverse relation which is seen between leptin and thyroid hormone levels.…”
Section: Leptin and The Thyroid Axissupporting
confidence: 70%
“…However, none of the two hormones measured in our study because of their known circadian rhythm are likely to be involved. Tri-iodothyronine administration to hypothyroid rats actually resulted in a rapid decrease in ob mRNA (22). Glucocorticoids have been shown to potently stimulate ob gene expression and leptin secretion in rats and in man, both in vivo and in vitro (23)(24)(25).…”
Section: Figurementioning
confidence: 99%